"Experimental study on performance and emissions of a turbochrged diesel engine fuelled with diesel and Vegetable oils blended with Ethanol". (2018) - Yerrennagoudaru, Hiregoudar; Manjunatha, K.; Kishore Kumar, K.S.
Abstract: In view of increasing pressure on crude oil reserves and environmental degradation as an outcome, fuels like Ethanol blended with Apricot oil, Pogamia oil, Cotton seed oil may present a sustainable solution as it can be produced from a wide range of carbon based feedstock. The present investigation evaluates Ethanol blended with Apricot oil, Pogamia oil, Cotton seed oil as a diesel engine fuel. The objectives of this paper is to analyze the fuel consumption and the emission characteristic of a twin cylinder diesel engine that are using Ethanol blended with Apricot oil, Pogamia oil, Cotton seed oil & compared to usage of ordinary diesel that are available in the market. A Twin cylinder diesel engine was adopted to study the brake thermal efficiency, brake specific energy consumption, and emissions at zero load & full load with the fuel of ethanol. In this study, the diesel engine was tested using Ethanol blended with Apricot oil, Pogamia oil, Cotton seed oil. By the end of the experiment, the successful of the experiment have been started which is Diesel engine is able to run with Ethanol blended with Apricot oil, Pogamia oil, Cotton seed oil but the engine needs to run by using diesel fuel first, then followed by Ethanol blended with Apricot oil, Pogamia oil, Cotton seed oil and finished with diesel fuel as the last fuel usage before the engine turned off. The performance of the engine using Ethanol blended with Apricot oil, Pogamia oil, Cotton seed oil fuel compared to the performance of engine with diesel fuel. Experimental results of Ethanol blended with Apricot oil, Pogamia oil, Cotton seed oil and Diesel fuel are also compared.